Kuasa Mengajar Sebagai Pelayanan Seorang Uskup - Paulus Tolo (Jurnal Alternatif Wacana Ilmiah Interkultural, 2020)
Teaching authority in Roman Catholic is entrusted to apostolic college of bishops with Pope as its head. This authoriy has been developed from the ouset of christianism. It is believed that the the apostolic college has handed over to bishops as their successor. The teaching authority performed by bishop is restricted to faith and moral matter. Their teachings in these matters obtain an infallible character. As far as the faith and moral matter are concerned, the infallibel character is accepted. Issues regarding politics, economics and so on are not in domain of the teaching authority of Magisterium. Catholics are strongly recommended to give their obbedience to the teachings of Magisterium. Are there possibilities to dissent from these teachings? This article demonstrates historical development of teaching authority in roman catholic and its implementation.